The first five seconds in the life of a clathrin-coated pit - Cocucci, Emanuele; Boulant, Steeve (Cell, 2012)
Summary Coated pits assemble by growth of a clathrin lattice, which is linked by adaptors to the underlying membrane. How does this process start? We used live-cell TIRF imaging with single-molecule EGFP sensitivity and high temporal resolution to detect arrival of the clathrin triskelions and AP2 adaptors that initiate coat assembly. Unbiased object identification and trajectory tracking, together with a statistical model, yield the arrival times and numbers of individual proteins, as well as experimentally confirmed estimates of the extent of substitution of endogenous by expressed, fluorescently tagged proteins. Pits initiate by coordinated arrival of clathrin and AP2, which is usually detected as two sequential steps, each of one triskelion with two adaptors. PI-4,5-P2 is essential for initiation. The accessory proteins FCHo1/2 are not; instead, they are required for sustained growth. This objective picture of coated pit initiation also shows that methods outlined here will be broadly useful for studies of dynamic assemblies in living cells.
Gesehen am 07.11.2018